Pro-con debate on regionalization of emergency general surgery: controversy or common sense? - Santry, Heena (Trauma Surg Acute Care Open, 2019)
More than three million patients every year develop emergency general surgical (EGS) conditions and this number is rising. EGS diseases range from straightforward to potentially life-threatening, and if severe or complex may require extensive resources. Given the looming surgeon shortage and concerns about access to care, regionalization of EGS care, in a manner similar to trauma care, has been proposed. We present a unique pro–con debate highlighting the salient arguments for and against regionalization of EGS care in the USA.